MRI-Guided Tumor Margin Assessment in Breast Cancer Surgery: Implications for Plastic and Cosmetic Breast Reconstruction - Wasim Ahmad, Zahid Iqbal Bhatti, Tanvir Ahmad, Irfan Ishaq, Khizer Abbas, Naveed Ahmad Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Achieving clear tumor margins in breast-conserving surgery is essential to reduce re-excision rates and improve oncological and cosmetic outcomes. Traditional margin assessment methods have limitations in accuracy. MRI-guided intraoperative margin assessment offers superior imaging, potentially enhancing surgical precision. This study evaluates its effectiveness and implications for reconstructive breast surgery. Methodology: This prospective study was conducted at Surgery and Radiology departments, of Mufti Mehmood Teaching Hospital DI Khan and Aziz Bhatti Shaheed Hospital, Gujrat, over a period of 12 months. A total of 82 female patients undergoing breast-conserving surgery (BCS) for histopathologically confirmed breast cancer were included. Intraoperative MRI was used to assess tumor margins, and findings were compared with final histopathological reports. Key outcomes included re-excision rates, accuracy of MRI margin assessment (sensitivity and specificity), operative time, and aesthetic outcomes. Statistical analyses, including chi-square tests, t-tests, and logistic regression models, were performed to determine the effectiveness of MRI guidance. Results: The mean tumor size measured intraoperatively by MRI was 2.8 cm, closely correlating with final histopathology measurements of 2.6 cm (p=0.032). The re-excision rate was 12.2%, significantly lower than conventional methods. MRI demonstrated 87.5% sensitivity and 92.3% specificity in detecting positive margins. The mean operative time for MRI-guided BCS was 135 minutes. Cosmetic outcomes were rated excellent by 42.7% of patients, and postoperative complications occurred in 13.4% of cases, comparable to traditional approaches. Conclusion: MRI-guided intraoperative margin assessment reduces re-excision rates and improves aesthetic outcomes without increasing complications. These findings support its integration in BCS and reconstructive surgery. Further studies are needed to confirm broader clinical applicability. Keywords: Breast Cancer Surgery, MRI-Guided Margin Assessment, Tumor Margins, Breast-Conserving Surgery, Re-Excision Rates, Aesthetic Outcomes, Plastic Surgery.